ANALYSIS OF SEGMENTING, TARGETING AND POSITIONING STRATEGIES ON CONSUMER PURCHASE DECISIONS IN THE DIGITAL ERA - Mery Berlian (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to test and analyze segmenting, targeting and positioning strategies for consumer purchasing decisions in the digital era. This type of research is quantitative research with causal associative relationship. The variables studied in this study are segmenting, targeting and positioning as the dependent variable and consumer purchasing decisions as independent variables. The subjects of this study were local fruit buyers in the city of Malang. The sample in this study were 100 respondents. The data analysis method used is validity test, reliability test, multiple regression analysis, F test, t test and dominant test. The results of this study indicate that the strategy of segmenting, targeting and positioning on consumer purchasing decisions in the digital era. These results explain that if the company wants to influence consumer purchasing decisions, the company should implement segmenting, targeting and positioning strategies, especially related to today's digital world where almost all consumers use it.